Book Reviews. (1st December 2011) - Harrison, Steven; Miley, Mike; Santiago, Norma Liz Rodriguez; Shutes, William; Vint, Sherryl
Voices in the Dark, Paul Kane and Marie O'Regan, (2011) Jefferson, NC: McFarland, 264 pp., ISBN 9780786446346 (pbk), $38.00 Dismantling the Dream Factory: Gender, German Cinema, and the Postwar Quest for a New Film Language, Hester Baer, (2009) New York: Berghahn Books, 304 pp., ISBN 9781845456054 (hbk), $90.00 Extra-Ordinary Men: White Heterosexual Masculinity and Contemporary Popular Cinema, Nicola Rehling, (2009) Lanham, MD: Lexington Books, 292 pp., ISBN 073912482X (hbk), $80.00 Ingmar Bergman: The Life and Films of the Last Great European Director, Geoffrey Macnab, (2009) London: I.B. Tauris, 242 pp., ISBN 9781848850460 (hbk), £19.95 The New-Brutality Film: Race and Affect in Contemporary Hollywood Cinema, Paul Gormley, (2005) Bristol: Intellect, 220 pp., ISBN 1-84150-119-0 (pbk), £19.95